Synthesis and Characterization of Metal Organic Frameworks Based on Samarium Metal and Perylene Ligand and Its Potential as a Photocatalysts (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2025)
Hydrogen is a renewable and environmentally friendly energy source that has significant potential as a substitute for fossil fuels. The energy contained in hydrogen per unit mass is greater than the energy of fossil fuels and other fuels. One of the methods that can be used to produce hydrogen is photocataytic water splitting using semiconductors. One of the semiconductor materials used for photocatalysis is metal organic frameworks (MOFs). MOFs have been extensively studied as photocatalysts for hydrogen gas production from water. This research aims to synthesize MOFs materials using samarium metal and perylene-3,4,9,10-tetracarboxylate (PTC) ligand through a solvothermal method at varying temperatures (100, 120, and 170 °C) for 24 hours, then characterized using FTIR, XRD, and DRS spectrophotometer, as well as its potential as a photocatalyst for hydrogen gas production. The synthesis results show that a temperature of 100 °C is the optimal reaction temperature. The FTIR analysis results show the presence of a bond between Sm and O at a wave number of 470-400 cm-1. The XRD results indicate that MOFs (Sm-PTC) are crystals with an average crystal size of 30-58 nm. The band gap energy obtained ranges from 1.8-2.0 eV at a maximum wavelength of 605-689 nm. Based on the characterization results, Sm-MOFs have the potential to be used as photocatalysts for hydrogen gas production.